Scalable coding of very high resolution video using the virtual zerotree - Qi Wang; Ghanbari, M. (IEEE transactions on circuits and systems for video technology, 1997)
Coding of HDTV and super high definition video requires not only high performance compression but also compatibility and scalability to satisfy transmission channels of various speeds and capacity and receivers working at different resolutions. A compatible and scalable coding scheme has been developed for these video signals. Wavelet decomposition is performed such that the low frequency band is of common intermediate format (CIF) order, which forms a low-resolution core of the full-sized video and is coded by MPEG. The high-frequency wavelet coefficients are coded by the proposed virtual zerotree which encodes the wavelet coefficients more efficiently than the simple zerotree. Also embedded in the scheme is the hierarchical motion compensation that gives high performance with a large capable compensation range, requires minimum computation, and reduces overhead motion information.